2003
DOI: 10.1002/chem.200304919
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Supramolecular Properties of Trimethylene‐Bridged Clips

Abstract: The novel trimethylene-bridged clips 3 and 4 have been synthesized by using repetitive stereoselective Diels-Alder reactions of the benzo- and naphthobismethylenenorbornenes 8 and 19 as dienes and norbornadiene 9 as bisdienophile, and subsequent dehydrogenation of the primary cyclobisadducts 10 and 20 by using 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ). Clips 3 and 4 serve as receptors for a variety of electron-deficient neutral and cationic aromatic substrates, comparable to the molecular tweezers 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 92 publications
0
29
0
Order By: Relevance
“…Monomers 2 and 3 were also prepared according to the literature procedures in multigram quantities. 34,35 Radical Polymerization. Emulsion polymerization of 1, carried out by Wood et al in 1960, 33 was reported to proceed exclusively via 1,4-addition, as characterized by infrared spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Monomers 2 and 3 were also prepared according to the literature procedures in multigram quantities. 34,35 Radical Polymerization. Emulsion polymerization of 1, carried out by Wood et al in 1960, 33 was reported to proceed exclusively via 1,4-addition, as characterized by infrared spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The only product isolated from the high-pressure reaction, in 66% yield, was the desired (2:1) DielsϪAlder adduct 7d, which could be converted into 1d by DDQ dehydrogenation in 14% yield. As a precursor to the naphthalene-spaced tweezers 2iϪn, the bis-dienophile 5i was prepared by enolization of the known diketone 18 [7,22,32] with DBU and subsequent nucleophilic substitution of ethyl bromoacetate with the resulting enolate (85% yield) (Scheme 6). A DielsϪAlder reaction between 5i and the diene 6a and subsequent DDQ oxidation of the resulting bis-adduct 8i gave the tweezer 2i.…”
Section: Synthesis Of the Substituted Tweezers 1d And 2i؊n And Of Thementioning
confidence: 99%
“…Molecular tweezers can in principle be divided into three groups: semirigid, [6][7][8][9][10][11][12][13] conformationally labile, [2,[14][15][16][17][18][19][20] and conformationally controlled by hydrogen bonds or metal chelation. [21][22][23] The interaction that mediates the recognition process can, in addition to London dispersion forces, be based on hydrogen-bonding, [24] charge-transfer, [14] ion-p, [8,25] p-p, [1] electrostatic, [8] and coupled interactions. [26] Most common are molecular tweezers with high symmetry, but there are some chiral examples.…”
Section: Introductionmentioning
confidence: 99%